Review On Importance Of Higher Education In Ethiopia: Implication For National Prosperity - Dr. Chala Wata Dereso (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The education reform of Ethiopia has been an impressive dimension since 1950. The expansion of education programmes in Ethiopia in the form of new universities, new courses, accelerating enrolments, institutional autonomy, curriculum revisions, new funding arrangements etc. are influencing national prosperity and boosting the development of an economy. In Ethiopia, the last two decades had been massive expansion of higher education but at the same time enrolment ratio, quality and relevance of the education system are the major challenges. Expanding higher education in any country needs vision and a strategy. Since its inception, the higher education in Ethiopia has been assuming that the modern education system followed by the western style is the only way to the development of higher education in Ethiopia. Still, the new education system is having few gaps i.e., lack of national interest, no clear directions for curriculum development and do not consider local situation or context. This study focuses on present higher education reform efforts in implication for national prosperity in Ethiopia, to analyse potential weaknesses in the higher education reform, to recommend appropriate changes for maintaining quality of education at a higher level.